Kajian Peraturan Jaksa Agung Nomor 15 Tahun 2020 Tentang Penghentian Penuntutan Berdasarkan Keadilan Restoratif - Andri Kristanto (Universitas Islam Indonesia, 2022)
The purpose of this study is to analyze: first, the study of the Attorney General's Regulation No. 15 of 2020 on the Termination of Prosecution Based on Restorative Justice in the perspective of restorative justice itself; second, the mechanism for stopping prosecution based on restorative justice based on the Prosecutor's Office Regulation No. 15 of 2020 has fulfilled the goal of protecting human rights. This legal research uses a normative juridical approach. The results of the study conclude that first, the findings of the data regarding the review of the Attorney General's Regulation No. 15 of 220 on the Termination of Prosecution Based on Restorative Justice indicate that: a) Article 3 of the Regulation of the Indonesian Attorney General's Regulation No. 15 of 2020 states that public prosecutors have the authority to close cases for legal purposes. b) Article 4 states that the termination of prosecution is carried out in the interests of the victim and other protected legal interests. c) Article 5 paragraph (5), which states for criminal acts in paragraphs (3) and (4) do not apply in the case of a casuistic situation which according to the consideration of the Public Prosecutor with the approval of the Head of the Branch Office of the District Attorney or the Head of the District Attorney's Office cannot be terminated. Second, the mechanism for implementing restorative justice in traffic accident cases consists of a) peace efforts. namely the peace process is carried out voluntarily, with deliberation for consensus, without pressure, coercion, and intimidation b) in the peace process there are two possible mechanisms, namely rejected or successful. The implementation of the peace agreement is divided into two ways, namely: 1) carried out by Payment of Compensation 2) carried out by doing something Key Words: Authority; attorney general's regulation; restorative justiceAbstrakTujuan dalam penelitian ini untuk menganalisis: pertama, kajian Peraturan Jaksa Agung Nomor 15 Tahun 2020 tentang penghentian penuntutan berdasarkan keadilan restoratif dalam perspektif restoratif justice. Kedua, mekanisme penghentian penuntutan berdasarkan keadilan restoratif berdasarkan Peraturan Jaksa Kejaksaan No. 15 Tahun 2020 tersebut telah memenuhi tujuan perlindungan Hak Asasi Manusia. Penelitian hukum ini menggunakan metode pendekatan yuridis normatif. Hasil penelitian menyimpulkan, pertama, temuan data mengenai kajian peraturan Jaksa Agung No 15 Tahun 220 tentang Penghentian Penuntutan Berdasarkan Keadilan Restoratif menunjukkan bahwa: a) dalam Pasal 3 Peraturan Kejaksaan RI No 15 Tahun 2020 menyatakan penuntut umum berwenang menutup perkara demi kepentingan hukum. b) Pasal 4 menyatakan penghentian penuntutan dilakukan atas kepentingan korban dan kepentingan hukum lain yang dilindungi. c) Pasal 5 ayat (5), yang menyebutkan untuk tindak pidana ayat (3) dan (4) tidak berlaku dalam hal terdapat keadaan kasuistik yang menurut pertimbangan Penuntut Umum dengan persetujuan Kepala Cabang Kejaksaan Negeri atau Kepala Kejaksaan Negeri tidak dapat dihentikan penuntutan. Kedua, mekanisme pelaksanaan keadilan restoratif dalam kasus kecelakaan lalu lintas terdiri dari a) upaya perdamaian. yaitu proses perdamaian dilakukan secara sukarela, dengan musyawarah untuk mufakat, tanpa tekanan, paksaan, dan intimidasi b) dalam proses perdamaian maka terdapat kemungkinan dua mekanisme yaitu ditolak atau berhasil. Pelaksanaan kesepakatan perdamaian yang terbagi dalam dua cara yaitu: 1) dilakukan dengan Pembayaran Ganti Rugi 2) dilakukan dengan melakukan sesuatu.Kata-kata Kunci: Wewenang; kejaksaan agung; keadilan restoratif